Efficient synthesis of gamma-keto sulfones by NHC-catalyzed intermolecular stetter reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Bhojgude, Sachin Suresh; Biju, Akkattu T. (Organic Letters, 2012)
The N-heterocyclic carbene-catalyzed intermolecular Stetter reaction of aldehydes with α,β-unsaturated sulfones allows the atom-economic and selective formation of γ-keto sulfones in good yields. Key to the success of this unique transition-metal-free carbon–carbon bond-forming reaction is the right choice of the NHC precursor and base. The reaction tolerates a broad range of different aldehydes.

Practical and general diels-alder reaction of pentafulvenes with arynes - Bhojgude, Sachin Suresh; Kaicharla, Trinadh; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2012)
A high-yielding, versatile and practical Diels–Alder reaction of pentafulvenes with arynes under mild reaction conditions is reported. The aryne generated by the fluoride induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes efficient cycloaddition with 6-substituted and 6,6-disubstituted pentafulvenes leading to the formation of benzonorbornadiene derivatives.

Recent advances in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions using arynes - Bhunia, Anup; Yetra, Santhivardhana Reddy; Biju, Akkattu T. (Chemical Society Reviews, 2012)
This tutorial review is aimed at highlighting recent developments in transition-metal-free carbon-carbon and carbon-heteroatom bond-forming reactions utilizing a versatile class of reactive intermediates, viz., arynes, which hold the potential for numerous applications in organic synthesis. Key to the success of the resurgence of interest in the rich chemistry of arynes is primarily the mild condition for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. Consequently, arynes have been employed for the construction of multisubstituted arenes with structural diversity and complexity. The versatile transition-metal-free applications of arynes include cycloaddition reactions, insertion reactions and multicomponent reactions. In addition, arynes have found applications in natural product synthesis. Herein, we present a concise account of the major developments that occurred in this field during the past eight years.

Multicomponent reactions involving arynes, quinolines, and aldehydes - Bhunia, Anup; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2013)
The multicomponent reaction involving arynes, quinolines, and aldehydes leading to the diastereoselective synthesis of benzoxazino quinoline derivatives in good yields proceeding via 1,4-zwitterionic intermediates is reported. In addition, the synthetic potential of various carbonyl compounds in this reaction as well as the utility of isoquinoline as the nucleophilic trigger has been examined.

NHC-Catalyzed reaction of enals with hydroxy chalcones: diastereoselective synthesis of functionalized coumarins - Bhunia, Anup; Patra, Atanu; Puranik, Vedavati G.; Biju, Akkattu T. (Organic Letters, 2013)
The N-heterocyclic carbene-catalyzed annulation of enals with 2'-hydroxy chalcones afford cyclopentane-fused coumarin derivatives with an excellent level of diastereocontrol. The reaction tolerates a broad range of functional groups; 25 examples are given, and a preliminary mechanistic investigation is provided.

Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and isatins - Bhunia, Anup; Roy, Tony; Pachfule, Pradip; Rajamohanan, Pattuparambil R.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2013)
Mix and match: With isoquinoline as the nucleophilic trigger, multicomponent reactions afforded spirooxazino isoquinoline derivatives, proceeding through 1,4-dipolar intermediates. The use of pyridine as a nucleophile furnished indolin-2-one derivatives, with the reaction likely proceeding through a pyridylidene intermediate.

Efficient synthesis of 9-aryldihydrophenanthrenes by a cascade reaction involving arynes and styrenes - Bhojgude, Sachin Suresh; Bhunia, Anup; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
A mild, general, and transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes is reported. The aryne generated by the fluoride-induced,1,2-elimination of 2-(trimethylsilyl)aryl triflates undergoes an efficient cascade reaction initiated by the Diels-Alder reaction with the differently substituted styrenes leading to the formation of 9-aryl-9,10-dihydrophenanthrene derivatives in moderate to good yields.

Employing arynes in transition-metal-free, N-heterocycles initiated multicomponent reactions - Bhunia, Anup; Biju, Akkattu T. (Synlett, 2014)
Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and various carbonyl compounds have been reported. With (iso)quinoline as the nucleophile and carbonyl compounds, such as aldehydes, ketones, and N-substituted isatins as electrophiles, the reaction afforded oxazino (iso)quinoline derivatives and the reaction proceeded via 1,4-dipolar intermediates. Interestingly, when the nucleophilic trigger used is pyridine, the reaction furnished indolin-2-one derivatives, and it is probable that the reaction proceeds via a pyridylidene intermediate.
Keywords: arynes - multicomponent reaction - oxindoles - pyridines - quinolines

Facile synthesis of gamma-ketophosphonates by an intermolecular stetter reaction onto vinylphosphonates - Patra, Atanu; Bhunia, Anup; Biju, Akkattu T. (Organic Letters, 2014)
The atom-economic and practical N-heterocyclic carbene (NHC) catalyzed Stetter reaction for the synthesis of gamma-ketophosphonates by the reaction of aromatic aldehydes with vinylphosphonates is reported. The NHC derived from N-mesitylimidazolium salt (IMes) was an effective catalyst for this transformation, and the products were formed in moderate to good yields.

Multicomponent reactions involving phosphines, arynes and aldehydes - Bhunia, Anup; Kaicharla, Trinadh; Porwal, Digvijay; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2014)
Although nucleophilic phosphine-catalysis is a powerful tool for the construction of various carbocycles and heterocycles, the reactions in which phosphines are incorporated into the final product are rare, and the reports on phosphine addition to highly electrophilic arynes are scarce. Herein, we report the phosphine triggered multicomponent reaction of arynes and aldehydes, which takes place via the formal [3+2] cycloaddition of an initially generated 1,3-phosphonium zwitterion from phosphines and arynes with aldehydes. The reaction resulted in the formation of a diverse range of stable pentacovalent phosphoranes in good yields based on the benzooxaphosphole system.

Rapid access to benzoxaphospholes and their spiro analogues by a three-component coupling involving arynes, phosphines, and activated ketones - Bhunia, Anup; Roy, Tony; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2014)
An operationally simple multicomponent coupling involving in situ generated arynes from 2 (trimethylsilyl)aryl triflates, phosphines, and various acyclic and cyclic activated carbonyl compounds has been developed. The reaction proceeds via a formal [3 + 2] cycloaddition mode giving access to differently substituted (spiro)benzoxaphosphole derivatives in moderate to good yields Mild reaction conditions. a broad scope. and the possibility of varying all the three-components are the notable features of the present reaction.

Synthesis of functionalized coumarins and quinolinones by NHC-catalyzed annulation of modified enals with heterocyclic C-H acids - Yetra, Santhivardhana Reddy; Roy, Tony; Bhunia, Anup; Porwal, Digvijay; Biju, Akkattu T. (Journal of Organic Chemistry, 2014)
N-Heterocyclic carbene (NHC) catalyzed lactonization and lactamization of 2-bromoenals with heterocyclic C–H acids proceeding via the α,β-unsaturated acyl azolium intermediates is reported. The reaction furnished coumarin- or quinolinone-fused lactone/lactam derivatives. In addition, results of the enantioselective version of this reaction using chiral NHC are presented.

Diastereoselective synthesis of cyclopentanone-fused spirooxindoles by N-heterocyclic carbene-catalyzed homoenolate annulation with isatilidenes - Patra, Atanu; Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Chemistry Frontiers, 2015)
N-Heterocyclic carbene (NHC)-catalyzed formal [3 + 2] annulation of α,β-unsaturated aldehydes with N-substituted isatilidenes resulting in the diastereoselective synthesis of cyclopentanone-fused spirooxindoles is demonstrated. Mechanistically, the reaction proceeds via the generation of homoenolate equivalent intermediates from NHC and enals, which on interception with isatilidenes afford spiroheterocyclic compounds bearing an all-carbon quaternary spiro-center in moderate to good yields and generally with high diastereoselectivity. Moreover, the functionalization of the spirooxindoles as well as the initial studies on the enantioselective version of this reaction are presented.

Reaction of N-heterocyclic carbenes with chalcones leading to the synthesis of deoxy-breslow intermediates in their oxidized form - Bhunia, Anup; Thorat, Shridhar H.; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2015)
The synthesis of deoxy-Breslow intermediates in their oxidized form has been developed via the reaction of N-heterocyclic carbenes (NHCs) with chalcones. Moreover, the initial tetrahedral adduct formed from the 1,4-addition of NHCs to chalcones is also isolated.

Employing arynes in diels–alder reactions and transition-metal-free multicomponent coupling and arylation reactions - Bhojgude, Sachin Suresh; Bhunia, Anup; Biju, Akkattu T. (Accounts of Chemical Research, 2016)
Conspectus <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Arynes are highly reactive intermediates having several applications in organic synthesis for the construction of various ortho-disubstituted arenes. Traditionally, arynes are generated in solution from haloarenes under strongly basic conditions. However, the scopes of many of the aryne reactions are limited because of the harsh conditions used for their generation. The renaissance of interest in aryne chemistry is mainly due to the mild conditions for their generation by the fluoride-induced 1,2-elimination of 2-(trimethylsilyl)aryl triflates. This Account is focused on the Diels–Alder reaction of arynes and their transition-metal-free application in multicomponent couplings as well as arylation reactions. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">The Diels–Alder reaction of arynes is a powerful tool for constructing benzo-fused carbocycles and heterocycles. In 2012, we developed an efficient, broad-scope, and scalable Diels–Alder reaction of pentafulvenes with arynes affording benzonorbornadiene derivatives. Subsequently, we accomplished the Diels–Alder reaction of arynes with dienes such as 1,2-benzoquinones and tropones. Moreover, we uncovered a transition-metal-free protocol for the synthesis of 9,10-dihydrophenanthrenes by the reaction of arynes with styrenes that proceeds via a Diels–Alder/ene-reaction cascade. In addition, we demonstrated the reaction of arynes with indene/benzofurans, which proceeds via a tandem [4 + 2]/[2 + 2] sequence. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Multicomponent coupling (MCC) involving arynes mainly comprises the initial addition of a nucleophile to the aryne followed by interception of the aryl anion intermediate with an electrophile (provided the nucleophilic and electrophilic moieties do not belong to the same molecule). We have disclosed aryne MCCs initiated by N-heterocycles such as (iso)quinoline, pyridine, and aziridines. When (iso)quinoline is used as the nucleophilic trigger and N-substituted isatin as the third component, the reaction affords spirooxazino(iso)quinolines via 1,4-dipolar intermediates. Unexpectedly, using pyridine affords indolin-2-ones, where the reaction proceeds via the pyridylidene intermediate. Additionally, we developed the phosphine-triggered aryne MCCs for the synthesis of functionalized benzooxaphospholes. In another phase of our work, we studied the synthetic utility of CO2 as a one-carbon synthon in aryne MCCs for the synthesis of phthalimides. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Engaging arynes as an aryl source is one of the transition-metal-free methods for arylation reactions. We have demonstrated the N-arylation of aromatic tertiary amines and O-arylation of aliphatic alcohols using arynes. <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">It is anticipated that the chemistry of arynes will continue to prosper and will lead to surprising developments for the synthesis of various 1,2-disubstituted arenes of molecular complexity and structural diversity. Future challenges in this area include the utility of arynes in enantioselective transformations and the synthesis and reactions of exotic heterocyclic arynes.
Keywords: 2-Benzoquinones; Cycloaddition; Facile N-arylation; O-arylation; One-Pot; Aldehydes; Benzyne; Amines; Heterocycles; Acids; 1

Synthesis of 4H-chromenes by an unexpected, K3PO4-mediated intramolecular rauhut–currier type reaction - Bhunia, Anup; Yetra, Santhivardhana Reddy; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2016)
In an attempt to develop the umpolung of Michael acceptors using chalcones having an enoate moiety under N-heterocyclic carbene (NHC) catalysis, a K3PO4-mediated intramolecular Rauhut–Currier type reaction was observed. This C(sp2)–C(sp2) coupling reaction afforded the biologically important 4H-chromenes in moderate to good yields. It is likely that the enol ether functionality acts as the nucleophilic trigger in this reaction.

Enantioselective synthesis of spiro γ-butyrolactones by N-heterocyclic carbene (NHC)-catalyzed formal [3+2] annulation of enals with 3-hydroxy oxindoles - Mukherjee, Subrata; Joseph, Sumi; Bhunia, Anup; Gonnade, Rajesh Ghanshyam; Reddy, Santhi Vardhan; Biju, Akkattu T. (Organic & Biomolecular Chemistry, 2017)
The N-heterocyclic carbene (NHC)-catalyzed enantioselective formal [3 + 2] annulation of α,β-unsaturated aldehydes with 3-hydroxy oxindoles is presented. Under oxidative conditions using the bisquinone oxidant, the reaction resulted in the synthesis of spiro γ-butyrolactones in moderate to good yields, enantioselectivity and diastereoselectivity. The reaction likely proceeds via the generation of the NHC-bound α,β-unsaturated acylazolium intermediate from enals, which was intercepted by the dioxindoles in a formal [3 + 2] pathway to form the spirocyclic compounds. However, a deeper mechanistic investigation revealed that the reaction can also proceed via the homoenolate intermediate. In this case, the dioxindole was oxidized to the corresponding isatin derivative using traces of air under basic conditions, and was intercepted with the NHC-bound homoenolate intermediate in a formal [3 + 2] pathway to afford the spiro compound.

Employing arynes for the generation of aryl anion equivalents and subsequent reaction with aldehydes - Gaykar, Rahul N.; Bhunia, Anup; Biju, Akkattu T. (Journal of Organic Chemistry, 2018)
Arynes are highly reactive intermediates, which are utilized for the electrophilic arylation of various X-H bonds (X = O, N, S etc.). Herein, a new synthetic strategy is demonstrated, where arynes are converted into aryl anion equivalents by treatment with phosphines and a base. The addition of phosphines to arynes form the phosphonium salts, which in the presence of a carbonate base generates the aryl anion equivalent. Subsequent addition of the aryl anions with aldehydes afforded the secondary alcohols.